Изменчивость форм черешни и вишни по величине урожая плодов - Талыбов, Т.Г.; Багиров, О.Р. (Фактори експериментальної еволюції організмів, 2009)
Cherry and sour cherry cultivating was widely spread in Nakhchivan AR where centralized its aboriginal sortiment. In the territory determined 26 sorts (9 introduced) and 35 forms of cherry, also 12 sorts (4 introduced) and 10 forms of sour cherry. Biomorphological and pomological characteristics of determined new prosperous sorts and forms have been learnt. Average fruit crop taken from observed fast-ripening trees were 29,5-35,0 kg, from mid- ripening trees were 29,5-40,5 kg and from late- ripening trees were 21,9-31,2 kg. For the past 4 years according to amount of fruit crop from fast- ripening forms of cherry Kotam-1 (142,6 kg) and sour cherry Bulgan-1 (158,6 kg); from mid- ripening forms of cherry Bashkant-3 (162,6 kg) and sour cherry Kotam-2 (155,2 kg); from late- ripening forms of cherry Kuku-1 (149,6 kg) were the best ones. Ecological coefficient of variation of the fruit crop taken from observed forms of cherry and sour cherry was between 17-66,8 %